Financial Sector Assessment Program - Poland : Credit Union Sector Regulatory and Supervisory Framework in Transition - World Bank (Washington, DC, 2014)
A World Bank-International Monetary Fund (IMF) mission visited Warsaw February 19 - March 5, 2013, to undertake an update of the Financial Sector Assessment Program (FSAP) conducted in 2006. The team was led by Luc Everaert (IMF) and Brett Coleman (World Bank) and included Karl Driessen, Nancy Rawlings, Yinqiu Lu, Jorge Chan-Lau, Rishi Ramchand (all IMF), Katia D'Hulster, Heinz Rudolph, Andrey Milyutin, John Pollner, Ignacio Tirado (all World Bank), as well as external experts David Walker (Canadian Deposit Insurance Corporation), Monnie Biety (independent consultant), and Fernando Montes-Negret (former World Bank and IMF). This note is prepared by Monnie Biety. The primary focus of this note is on the legal, regulatory, and supervisory framework of Poland's credit unions (SKOKs) at a time when the authorities are transitioning them to a stronger, more stable footing. The note reviews the law, regulations, and supervision regime in force at the time of the FSAP mission and suggests ways to help strengthen the SKOKs in a phased manner that gives viable SKOKs the necessary time and support to meet the new requirements. While the draft law was not reviewed during the FSAP as it was anticipated that there were to be many changes to the draft, key aspects of the draft law were analyzed using information and reports gathered that discussed the contents of the law. The note concludes with a discussion of these elements of the draft law. Numeric data used in this report were provided by National Association of Savings and Credit Unions (NASCU) during the FSAP mission, with some corrections provided by KNF post mission.